REVISITING THE ENGLISH STATUS IN THE OUTER AND EXPANDING CIRCLES: INSIGHTS FROM GOOGLE STREET VIEW® - Kurniawan, Hasyim; Moehkardi, Rio; Muliawati, Nabila (LLT Journal: A Journal on Language and Language Teaching, 2024)
Globalization and glocalization may affect the use of English in Kachru’s (1986) Outer Circle and Expanding Circle countries. This study revisits the status of English by observing its use in the commercial signboards in Malaysia (Petaling Street) and the Philippines (Colon Street), representing the Outer Circle, Thailand (Khao San Road), and Indonesia (Legian Street), representing the Expanding Circle. Using Google Street View®, 557 signages were screen-captured, and their brand names, information, and slogan parts were analyzed. The finding shows that English is predominant on almost all signboard parts on the four streets, showcasing its crucial role in building brand identity and efficacy for communicating with a wider market. Furthermore, linguistic strategies such as code-mixing are pervasive in both circles, indicating the norm-developing characteristic not only in the Outer but also in the Expanding Circle. Language regulation enforcement may affect the degree of visibility of English, but its prevalence remains high nonetheless. Overall, the traditional conception of these concentric circles needs to be reanalyzed and a more fluid model needs to be put forward.